2010
DOI: 10.1038/nchem.626
|View full text |Cite
|
Sign up to set email alerts
|

Using first principles to predict bimetallic catalysts for the ammonia decomposition reaction

Abstract: The facile decomposition of ammonia to produce hydrogen is critical to its use as a hydrogen storage medium in a hydrogen economy, and although ruthenium shows good activity for catalysing this process, its expense and scarcity are prohibitive to large-scale commercialization. The need to develop alternative catalysts has been addressed here, using microkinetic modelling combined with density functional studies to identify suitable monolayer bimetallic (surface or subsurface) catalysts based on nitrogen bindin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
327
0
3

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 418 publications
(345 citation statements)
references
References 39 publications
15
327
0
3
Order By: Relevance
“…The adsorbed ammonia molecule undergoes successive N-H bond cleavage, releasing hydrogen atoms than can combine to form molecular hydrogen. The final step involves the recombinative desorption of nitrogen adatoms to yield molecular nitrogen [22]. Interestingly, even though the decomposition of ammonia is the reverse of the synthesis, catalyst do not necessarily exhibit the same activity in both directions due to a difference in rate limiting step as discussed in the work by Boisen et al [23].…”
Section: Mechanism Of Ammonia Decomposition Over Heterogeneous Catalystsmentioning
confidence: 96%
See 2 more Smart Citations
“…The adsorbed ammonia molecule undergoes successive N-H bond cleavage, releasing hydrogen atoms than can combine to form molecular hydrogen. The final step involves the recombinative desorption of nitrogen adatoms to yield molecular nitrogen [22]. Interestingly, even though the decomposition of ammonia is the reverse of the synthesis, catalyst do not necessarily exhibit the same activity in both directions due to a difference in rate limiting step as discussed in the work by Boisen et al [23].…”
Section: Mechanism Of Ammonia Decomposition Over Heterogeneous Catalystsmentioning
confidence: 96%
“…The use of first principle calculations and interpolation across the periodic table has identified CoMo as an attractive bimetallic candidate to substitute ruthenium based catalysts for the production of hydrogen from ammonia [22,89,98]. As shown in Fig.…”
Section: Bimetallic Systemsmentioning
confidence: 99%
See 1 more Smart Citation
“…77 The volcano plot is a quantitative manifestation of Sabatier's principle and is widely used in both gas-phase heterogeneous catalysis and electrocatalysis. 28,55,68,[78][79][80][81][82][83][84][85][86][87] It is important to stress that the dashed line on the volcano plot in Fig. 5 represents an upper limit to the activity that we would expect for a metal surface.…”
Section: Theoretical Trends In Activity For Pt and Its Alloysmentioning
confidence: 99%
“…In this regard, the development of high-performance ammonia decomposition catalysts would be of significant importance for an ammonia-mediated hydrogen economy. Although research effort focused on the catalysis of ammonia decomposition has increased rapidly in recent years [21][22][23][24][25][26][27][28][29][30], and the catalytic activity of current catalysts still requires significant improvement because the current level of ammonia conversion remains much lower than the equilibrium, particularly at reaction temperatures lower than 400 • C. Research progress has identified that Ru is currently the most active component for ammonia decomposition. The control of Ru particles with optimal size and morphology is very important in ammonia decomposition since ammonia decomposition with Ru is structure-sensitive due to the variation of highly active B 5 -type sites [31,32].…”
Section: Introductionmentioning
confidence: 99%